African and Asia-Pacific Regional Trade Agreements: A Comparative Analysis - Olalekan, Olatunbosun (AFEBI Economic and Finance Review, 2024)
This study compares the African Continental Free commerce Area (AfCFTA) and the Regional Comprehensive Economic Partnership (RCEP) on regional trade, economic growth, and geopolitics. This study examines how these agreements affect regional trade and economic integration using a thorough evaluation of recent empirical data and theoretical frameworks. A comprehensive literature analysis, data extraction, and quality assessment from multiple academic databases for 2010–2024 research are used. AfCFTA is projected to expand intra-African trade especially the manufacturing and agriculture sector, and is anticipated to enhance Africa's GDP. RCEP has increased trade volumes also. According to Viner's theory of trade formation and diversion, these agreements are crucial to economic stability and regional cooperation. This study sheds light on regional trade agreements' economic benefits and encourages future research on their long-term socio-economic and policy ramifications.